Mars' Ionopause: A Matter of Pressures. Issue 9 (18th September 2020) - Sánchez‐Cano, Beatriz; Narvaez, Clara; Lester, Mark; Mendillo, Michael; Mayyasi, Majd; Holmstrom, Mats; Halekas, Jasper; Andersson, Laila; Fowler, Christopher M.; McFadden, James P.; Durward, Sofija
Abstract: This study assesses under what circumstances the Martian ionopause is formed on the dayside, both in regions where there are strong crustal magnetic fields and areas where these fields are small (<30 nT). Multiple data sets from three MAVEN dayside deep dip campaigns are utilized between periapsis and 600–1, 000 km, as well as solar wind observations from Mars Express. The ionopause is identified as a sudden decrease of the electron density with increasing altitude and a simultaneous increase of the electron temperature and variability below 400 km. This is a physically robust approach as the electron temperature is a key parameter in determining the structure of the ionospheric profile, and, therefore, also a strong indicator of the ionopause location. We find that 36% (54%) of the electron density profiles over strong (weak) crustal magnetic field regions had an ionopause event. We also evaluate the roles of ionospheric thermal and magnetic pressures on the ionopause formation as well as the presence of solar wind particles, H +, down to the location of the ionopause. We found that the topside ionosphere is typically magnetized at mostly all altitudes. The ionopause, if formed, occurs where the total ionospheric pressure (magnetic + thermal) equals the upstream solar wind dynamic pressure. Moreover, the lower edge of the ionopause coincides with the altitude where the solar wind flow stops: The thermal pressure suffers a significant reduction with increasing altitude and the solar wind proton density has a prominent increase. Plain Language Summary: The ionosphere of Mars is the layer of its atmosphere where gases are separated into ions and electrons by solar radiation. The ionopause is the uppermost region where the ionosphere terminates. However, the Martian ionopause is not well‐understood because it does not always form, and when it does, it is located over a large range of altitudes, varies rapidly, and is highly structured. This paper does a statistical analysis of the different parameters that play a role in ionopause formation, both over and far from the strong Martian crustal magnetic field regions. The study focuses on observations from the dayside of Mars, and analyzes several data sets from the MAVEN and Mars Express missions. It is found that the ionosphere almost always contains magnetic fields within it and that there is a pressure balance at its upper boundary (the ionopause) between the solar wind and the ionosphere. Moreover, there are more ionopause events far from the surface magnetic field regions than over them. Key Points: Mars' ionopause identification is based on simultaneous electron density and electron temperature changes When the Martian ionopause is formed, the upstream solar wind dynamic pressure is enough to equal the total pressure of the ionosphere Fewer ionopauses are identified over strong crustal magnetic fields because the total ionospheric pressure is larger and excludes the solar wind from penetrating into the ionosphere